Fabrication and characterization of high-performance Mo-doped TiN coatings. (August 2021) - Zhou, Shenghao; Zhao, Weichen; Wu, Yaosha; Qiu, Zhaoguo; Lin, Songsheng; Zheng, Zhigang; Zeng, D.C.
Abstract: To realize the fabrication of Ti–Mo–N coatings with novel properties predicted towards industrial applications, Mo-doped TiN coatings have been fabricated by multi-arc ion plating with varied substrate bias, and systematically characterized. The as-deposited coatings show a 1.5 at% Mo content deficit due to melting point difference between Mo and Ti elements. X-ray diffraction (XRD) and X-ray photoelectron spectrum (XPS) results show the as-deposited coatings demonstrate a fcc-TiN + bct-Ti2 N dual phase structure, with Mo solution into TiN lattice. The hardness of TiMo0.08 N coatings is above 31.97 GPa, which first increases then decreases slightly, peaking at 34.26 GPa. The phenomenon is correlated to the decreased (111) while enhanced (220) preferred orientation. All coatings show adhesion properties above 65 N (>100 N when bias voltage is above −50 V) and friction coefficients (COFs) below 0.24, which is attributed to the formation of lubricant MoO3 phase in a surface tribochemical process, as confirmed by XPS and Raman spectra evidences. Electrochemical polarization curves reveal that all samples have higher corrosion potential and corrosion currents two order of magnitudes lower than the WC-Co substrates. Additionally, substrate bias voltage has little impacts on structures and properties of the coatings, which means a wide process window. Highlights: The TiMo0.08 N coatings have hardness above 32 GPa and excellent adhesion strength. All samples show solid lubricating effect with COFs below 0.24. The coatings show good corrosion resistance. The coatings demonstrate a broad substrate bias voltage window.